Related Model (Connected): Development of Integrated Social Studies Learning Module - Maulinda, Dewi (EDUPEDIA Publisher, 2022)
Abstract: This article is based on the development research to produce Module Education of Social Science Unity Based Connected Mode in learning. Model development is adapting from Dick and Carey's design. The present model validation by some experts, such as social sciences and teachers' learning. It also has been tested on the students of the seventh grade at the MTCN 4 Kota Jambi. The result revealed that the product (module education of social science unity-based connected mode) improves students' knowledge and makes learning meaningful and fun.